(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
Suffer most of the industrial sector companies from high Kperfi magnitude of the costs of industrial indirect, lack of equitable distribution of these costs on the objectives of cost, increased competition, and the lack of proper planning in line and changes faced by the industrial sector (general) and sample (private), as well as the difficulty in re- directing efforts to improve profitability and in-depth analysis of activities, and to identify untapped resource activities, then link these activities to the final products The research aims to apply the technology review and evaluate programs with the method (ABC) through the application stages of planning, scheduling and control and a comparison to get to the products of deviations Department knitting socks and put several alternatives to the management for the purpose of decision-making. And for the purpose of access to the goal of research The research was based on a fundamental premise (that the use of technical review and evaluate programs lead to understanding and improving the implementation of the cost method on the basis of activity). It adopted a researcher at the theoretical side on the method of inductive sources, references and research available in the international information network (Internet), but the practical side has been relying on the descriptive approach through the financial statements, interviews, and meetings with officials in the company sample, as well as follow-up field.